Mitochondrial double-stranded RNAs as a pivotal mediator in the pathogenesis of Sjӧgren's syndrome - Jimin Yoon; Minseok Lee; Ahsan Ausaf Ali; Ye Rim Oh; Yong Seok Choi; Sujin Kim; Namseok Lee; Se Gwang Jang; Seonghyeon Park; Jin-Haeng Chung; Seung-Ki Kwok; Joon Young Hyon; et al. (Elsevier, 2022)
Sjӧgren's syndrome (SS) is a systemic autoimmune disease that targets the exocrine glands, resulting in impaired saliva and tear secretion. To date, type I interferons (I-IFNs) are increasingly recognized as pivotal mediators in SS, but their endogenous drivers have not been elucidated. Here, we investigate the role of mitochondrial double-stranded RNAs (mt-dsRNAs) in regulating I-IFNs and other glandular phenotypes of SS. We find that mt-dsRNAs are elevated in the saliva and tears of SS patients (n = 73 for saliva and n = 16 for tears) and in salivary glands of non-obese diabetic mice with salivary dysfunction. Using the in-house-developed 3D culture of immortalized human salivary gland cells, we show that stimulation by exogenous dsRNAs increase mt-dsRNAs, activate the innate immune system, trigger I-IFNs, and promote glandular phenotypes. These responses are mediated via the Janus kinase 1 (JAK1)/signal transducer and activator of transcription (STAT) pathway. Indeed, a small chemical inhibitor of JAK1 attenuates mtRNA elevation and immune activation. We further show that muscarinic receptor ligand acetylcholine ameliorates autoimmune characteristics by preventing mt-dsRNA-mediated immune activation. Last, direct suppression of mt-dsRNAs reverses the glandular phenotypes of SS. Altogether, our study underscores the significance of mt-dsRNA upregulation in the pathogenesis of SS and suggests mt-dsRNAs as propagators of a pseudo-viral signal in the SS target tissue.